Improving efficiency of wireless charging system in electric vehicle using a hybrid ultracapacitor-battery energy storage approach - Fang, Liew Hui; Romli, Muhammad Izuan Fahmi; Rahim, Rosemizi Abd; Mukhtar, Nurhakimah Mohd; Kimpol, Norhanisa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
This research aims to enhance the efficiency of wireless charging systems in electric vehicles by integrating a hybrid ultracapacitor-battery energy storage solution. Traditional standalone battery-based energy storage systems in wireless charging often face sub-optimal charging efficiency, resulting in extended charging times and reduced energy transfer efficiency. To address this limitation, we propose a hybrid approach that combines the rapid charging capability of ultracapacitor (supercapacitor) with the long-term storage capacity of batteries. The optimal charging range is 0 cm to 2 cm, and the combined output voltage and current are 5 V to 12 V and 0.63 A, respectively. This hybrid energy storage system will significantly boost electric vehicles (EVs) charging efficiency. Our research involves experimental evaluation and data analysis to assess crucial parameters, including charging efficiency, energy transfer efficiency, and charging time. The experimental results are validated and compared against existing battery-only systems, shedding light on the advantages and limitations of the hybrid approach. This study contributes to the optimization of wireless charging systems, enhancing energy transfer efficiency, and promoting the broader adoption of wireless charging technology in electric vehicles.